1987
DOI: 10.1139/b87-215
|View full text |Cite
|
Sign up to set email alerts
|

A survey of endosperm starch granules in the genus Hordeum: a study using image analytic and numerical taxonomic techniques

Abstract: Image analysis was used to quantify size of endospermic starch granules in 39 species of Hordeum. A set of 279 samples, each with ca. 25 replicates, representing most species of the genus was analyzed by various multivariate techniques. Two groups can be distinguished. One group consisting of 6 species (H. vulgare, H. spontaneum, H. bulbosum, H. glaucum, H. murinum, and H. leporinum) is characterized by possessing granules greater than 35 μm in diameter and a bimodal distribution of all the sizes. The second g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…Scanning electron micrographs (SEM) showed that both mutant and wild type had two types of starch granules, large A in lenticular shape and small B in spherical shape as the previous report [42], whereas a few irregular-shaped granules were observed in WRS-1 ( Table 2 and Fig. (3)).…”
Section: Starch Granule Morphologysupporting
confidence: 66%
“…Scanning electron micrographs (SEM) showed that both mutant and wild type had two types of starch granules, large A in lenticular shape and small B in spherical shape as the previous report [42], whereas a few irregular-shaped granules were observed in WRS-1 ( Table 2 and Fig. (3)).…”
Section: Starch Granule Morphologysupporting
confidence: 66%
“…The wheat starch showed the presence of spherical, lenticular shaped, and large disc like granules having large proportion of A-type granules and small proportion of B-type granules. Baum and Bailey [46] reported that wheat endosperm consist of two types of starches during maturity, that is, large (A-type) and small (B-type). The granules of rice were observed to be polygonal, hexagonal, irregular, and angular shaped.…”
Section: Granular Characteristicsmentioning
confidence: 99%
“…The proportions of individual size fractions of starch granules are likely to be influenced by varietal factors. This has been confirmed by a number of authors 2,6,9,15,18 . At the observed variety set, the influence of varieties on the total variability of the ratio of small and large Results obtained by the means of the GFFF method confirmed the highly significant effect of variety (84%).…”
Section: )79087 %2( (-7'977-32mentioning
confidence: 56%